2019
DOI: 10.13057/biodiv/d200630
|View full text |Cite
|
Sign up to set email alerts
|

Growth pattern in tropical mangrove trees of Bunaken National Park, North Sulawesi, Indonesia

Abstract: Abstract. Djamaluddin R. 2019. Growth pattern in tropical mangrove trees of Bunaken National Park, North Sulawesi, Indonesia. Biodiversitas 20: 1713-1720. Seasonal diameter growth patterns in mangrove are often related to rainfall, temperature and moisture regime. At any localities, specific environmental factors may influence growth rate of individual trees. I asked whether stem growth of tropical mangrove in BNP is constant over a year, and whether stem growth rates are different by sites, species, and trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Sonneratia alba ); in Bunaken Timur the sand flats and aprons of the back reefs reached the seaward mangrove fringe and in Bunaken Papaboa (Liang beach) the forest colonized the seaward side of coral sand berms (Appendix SI, Supporting Information). In Pulau Mantehage, the basement was more eroded (maximum 15 m above mean sea level: Djamaluddin, ), forming wider intertidal zones (150–1000 m) covered by soft mud deposits, colonized by dense mangrove formations. All the mudskippers collected or observed throughout the study were found within 1–2 m from the water's edge, with few specimens found in burrows, up to 10 m from the water's edge.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Sonneratia alba ); in Bunaken Timur the sand flats and aprons of the back reefs reached the seaward mangrove fringe and in Bunaken Papaboa (Liang beach) the forest colonized the seaward side of coral sand berms (Appendix SI, Supporting Information). In Pulau Mantehage, the basement was more eroded (maximum 15 m above mean sea level: Djamaluddin, ), forming wider intertidal zones (150–1000 m) covered by soft mud deposits, colonized by dense mangrove formations. All the mudskippers collected or observed throughout the study were found within 1–2 m from the water's edge, with few specimens found in burrows, up to 10 m from the water's edge.…”
Section: Resultsmentioning
confidence: 92%
“…Consistently, Periophthalmus clade F and P . kalolo were found along the east coast of Mantehage Island, where barrier reefs are better developed (Djamaluddin, ; Fig. ) and offer a less extreme environment for larval settlement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations